Lessons Learned in The Knowledge Management Process - Tekhanmag, Kanda (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
Society has shifted to a knowledge - based society, where emphasize power is knowledge, a harmonious combination of value, truth, belief, ability, experience, insight, intuition and discretion, that a person may receive from many channels, especially the action or practice. Knowledge management is the extraction of tacit knowledge into explicit knowledge, that is concrete, easy to disseminate, and easy to understand, and can be used or applied for the benefit of work powerfully. In order to manage tacit knowledge into explicit knowledge, it is necessary to use correct and appropriate knowledge management techniques. The lessons learned process is both a knowledge management tool and a goal of knowledge management. By taking lessons learn process from good practice, participants in the process learn together at individual, group and organizational levels through the exchange of perspectives and experiences, causing a change in the way of thinking, creative way of working in higher quality, until the lessons can be taken to continuously enhance learning.